Tourism and its Socio-economic Effects on Tourism Villages of Kaski, Nepal - Subedi, Netra Prasad; Bhandari, Hari Bahadur (Janapriya Journal of Interdisciplinary Studies, 2019)
Tourism is one of the rapidly growing, complicated and multidimensional business activities worldwide. Village tourism carries high level of potentiality in the county like Nepal which is full of large number of villages having divergent cultures, caste, ethnic groups, climates, religions, and language speaker scattering from the Tarai to the Himalayan territories. This research paper has aimed to explore the socio-economic effects of village tourism activities and the key barriers for the development of village tourism. It has adopted descriptive cum analytical research design and conducted a survey in three sampled villages to collect primary data from75 respondents, 25 from each village including people directly involved in tourism activities and people not directly involved in tourism activities. The research result has revealed that village tourism activities have significant effects on education, lodging and food culture, government revenue, earnings capacity of the villagers and flow of domestic tourists without any adverse effect on religion and culture, youth of the villages and social undertakings. It has also revealed that there is statistically significant association across the sampled villages regarding socioeconomic effects. Furthermore, tourism education, transportation facilities, and lack of skilled manpower have been identified as the key barriers for the sustainable development of village tourism.